Peningkatan Menuliskan Kembali Dongen dengan Teknik CIRC Siswa Kelas VII.D SMPN 1 Tanjung Emas - Sari, Lisa Silvia; Nursaid, Nursaid; Asri, Yasnur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written that has purpose to describe and analyze the improving of rewriting skill of fairytale by using CIRC technique. Subject of this research is students at class VII.D at SMP Negeri 1 Tanjung Emas, Tanah Datar regency which consists at 20 students. Based on the research finding of rewriting fairytales skill by using CIRC technique of student at class VII.D at SMP Negeri 1 Tanjung Emas, Tanah Datar Regency can be concludd to some points. First the process of teaching rewriting faiytale by using CIRC technique is going better. Second the implementation of CIRC technique in two cycles (fourth time meeting) can improveÂ  students skill in rewriting of fairytale about 71,8%Â  in cycle 1 and then it is increasing in cycle II become 82,88%.